Biomass pretreatment method

By adding nucleophilic reagents to the acid pretreatment, the problem of lignin condensation hindering enzymatic decomposition under acid reaction conditions was solved, cellulose saccharification efficiency and cellulose accessibility were improved, and better conditions were provided for biomass conversion.

CN119753058APending Publication Date: 2025-04-04ANHUI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889394.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing acid pretreatment technology, acid reaction conditions cause irreversible condensation of lignin in lignocellulose, hinder cellulase hydrolysis and reduce biomass conversion efficiency.

Method used

The nucleophilic reagent is directly added during the acid pretreatment process to improve the characteristics of the pretreated substrate, improve the accessibility of cellulose, promote lignin decomposition, and improve the cellulose saccharification efficiency.

Benefits of technology

By adding nucleophilic reagent, the cellulose saccharification efficiency of the acid pretreatment material is significantly improved, the surface structure of the pretreatment material is improved, and better conditions are provided for further utilization of biomass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753058A_ABST
    Figure CN119753058A_ABST
Patent Text Reader

Abstract

The invention provides a biomass pretreatment method, which belongs to the technical field of biomass processing and utilization, and comprises the following steps: soaking crushed poplar in an acid solution according to a solid-to-liquid ratio of 1: 7 (w / v), adding a nucleophilic reagent into the solution, and reacting at 180 DEG C; after the reaction is finished, cooling a reaction system to room temperature, and carrying out solid-liquid separation to obtain a pretreated solid; rinsing the pretreated solid, washing the substrate with distilled water until the pH value is close to neutral, and rinsing for three times to obtain an acid-nucleophilic reagent pretreated material; the nucleophilic reagent is directly added in the acid pretreatment, so that the saccharification efficiency of the acid pretreatment biomass raw material is improved, the defect that the saccharification efficiency of the pretreated biomass cellulose in the existing acid pretreatment technology is limited is overcome, meanwhile, the characteristics of the pretreatment substrate are improved, the accessibility of the cellulose is improved, and the surface structure of the pretreated material is improved; better conditions are provided for further utilization of the biomass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomass processing and utilization, and in particular to a biomass pretreatment method. Background Art

[0002] As an abundant natural resource, lignocellulosic biomass, composed of cellulose, hemicellulose and lignin, is a potential sustainable raw material for the production of biofuels and high-value chemicals. Acid pretreatment is a widely used biomass pretreatment technology. By treating lignocellulose with low-concentration inorganic acids, the stubborn structure of biomass can be decomposed and the efficiency of subsequent bioconversion can be improved. However, one of the biggest development bottlenecks of this technology is that the acid reaction conditions during the pretreatment process will cause the lignin in the lignocellulose to generate new carbon-carbon bonds and undergo irreversible condensation, forming a physical barrier to the cellulase hydrolysis of the pretreated substrate, and at the same time, it works together with the fermentation inhibitors generated in the pretreated liquid to limit the enzymatic digestibility of the pretreated substrate. This hinders the subsequent enzymatic hydrolysis process and reduces the overall efficiency of biomass conversion. Summary of the invention

[0003] The purpose of the present invention is to overcome the defect of limited saccharification efficiency of cellulose in pretreated biomass materials in existing acid pretreatment technology, and provide a method for improving the saccharification efficiency of acid pretreated materials by directly adding nucleophilic reagents during acid pretreatment.

[0004] In order to achieve the above purpose and other purposes, the present invention is implemented by the following technical scheme: comprising the following steps:

[0005] S1, immersing the crushed poplar wood in an acid solution at a solid-liquid ratio of 1:7 (w / v), and adding a nucleophilic reagent to the solution for reaction at 180°C;

[0006] S2, after the reaction is completed, the reaction system in step S1 is cooled to room temperature, and solid-liquid separation is performed to obtain a pretreated solid;

[0007] S3, rinsing the pretreated solid obtained in step S2, washing the substrate with distilled water until the pH value is close to neutral, and performing the rinsing process three times to obtain an acid-nucleophile-pretreated material.

[0008] In one embodiment, the acid is phosphoric acid.

[0009] In one embodiment, the concentration of phosphoric acid is 1.5% (v / v).

[0010] In one embodiment, the nucleophile is ascorbic acid, 2-naphthol, 3-hydroxy-2-naphthoic acid or 2-naphthol-7-sulfonic acid.

[0011] In one embodiment, the amount of the nucleophile added is 4% (w / w biomass).

[0012] In one embodiment, the reaction time is 60 minutes.

[0013] The invention improves the characteristics of the pretreated substrate, increases the accessibility of cellulose, increases the cellulose saccharification efficiency of the acid pretreated material, and provides better conditions for further utilization of biomass by adding a nucleophilic reagent during the acid pretreatment process. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Shown are scanning electron microscope images of the pretreated materials of Examples 1 to 4 and Comparative Example 1 of the present invention.

[0015] Among them, (a) is the scanning electron microscope image of the pretreated material of comparative example 1; (b) is the scanning electron microscope image of the pretreated material of embodiment 1; (c) is the scanning electron microscope image of the pretreated material of embodiment 2; (d) is the scanning electron microscope image of the pretreated material of embodiment 3; (e) is the scanning electron microscope image of the pretreated material of embodiment 4.

[0016] Figure 2 It shows the enzymatic hydrolysis yield of the pretreated materials in Examples 1 to 4 and Comparative Example 1 of the present invention.

[0017] Figure 3 Shown are the XRD patterns of the pretreated materials of Examples 1 to 4 and Comparative Example 1 of the present invention.

[0018] Figure 4 Shown are XPS analysis charts of the pre-treated materials of Examples 1 to 4 and Comparative Example 1 of the present invention.

[0019] Among them, (a) is the XPS analysis diagram of the pretreated material of comparative example 1; (b) is the XPS analysis diagram of the pretreated material of embodiment 1; (c) is the XPS analysis diagram of the pretreated material of embodiment 2; (d) is the XPS analysis diagram of the pretreated material of embodiment 3; (e) is the XPS analysis diagram of the pretreated material of embodiment 4. DETAILED DESCRIPTION

[0020] The present invention will be further described below with reference to the embodiments.

[0021] Unless otherwise specified, all raw materials used in the examples are commercially available.

[0022] Example 1

[0023] This embodiment provides a biomass pretreatment method, which adds a nucleophilic agent during phosphoric acid pretreatment to improve the saccharification efficiency of lignocellulose, comprising the following steps:

[0024] S1, 50 g of crushed poplar wood was immersed in a 1.5% (v / v) phosphoric acid solution at a solid-liquid ratio of 1:7, and 4% (w / w) nucleophilic reagent ascorbic acid was added to the solution, and the solution was kept at 180° C. for 60 min, and the pressure was controlled to be 0.67 MPa;

[0025] S2, after the reaction is completed, the reaction system in step S1 is cooled to room temperature, and solid-liquid separation is performed to obtain a pretreated solid;

[0026] S3, washing the pretreated solid obtained in step S2 with distilled water until the pH value is close to neutral, and the rinsing process is performed three times to obtain a phosphoric acid-ascorbic acid-pretreated material; and storing the phosphoric acid-ascorbic acid-pretreated material at 4° C. for further cellulose saccharification.

[0027] Example 2

[0028] The difference between this embodiment and embodiment 1 is that the nucleophilic reagent added in the pretreatment is 2-naphthol.

[0029] Example 3

[0030] The difference between this embodiment and embodiment 1 is that the nucleophilic reagent added in the pretreatment is 3-hydroxy-2-naphthoic acid.

[0031] Example 4

[0032] The difference between this embodiment and embodiment 1 is that the nucleophilic reagent added in the pretreatment is 2-naphthol-7-sulfonic acid.

[0033] Comparative Example 1

[0034] The difference between this comparative example and Example 1 is that no nucleophilic reagent is added during the pretreatment process.

[0035] The reaction conditions of each embodiment and comparative example are shown in Table 1:

[0036] Table 1 Reaction conditions of examples and comparative examples

[0037] Pretreatment phosphate concentration (v / v) Pretreatment nucleophile type Example 1 1.5% ascorbic acid Example 2 1.5% 2-Naphthol Example 3 1.5% 3-Hydroxy-2-naphthoic acid Example 4 1.5% 2-Naphthol-7-sulfonic acid Comparative Example 1 1.5% none

[0038] Results Analysis

[0039] Analysis Example 1: Effect of Nucleophilic Reagent Addition on the Composition and Surface Physical and Chemical Properties of Physico-Physical Phosphoric Acid Pretreated Materials

[0040] The chemical composition analysis of the pretreated materials obtained in Examples 1 to 4 and Comparative Example 1 was performed respectively, and the results are shown in Table 2.

[0041] Table 2 Chemical composition analysis of pretreated materials

[0042]

[0043]

[0044] The ethanol extract is believed to be mainly composed of lignin decomposed during the pretreatment. As shown in Table 2, when the poplar wood is pretreated with phosphoric acid at 180°C for 60 minutes, the ethanol extract content in Examples 1 to 4 is 12.67% to 21.87%, and the ethanol extract content in Comparative Example 1 is 12.60%, which indicates that the addition of nucleophiles during phosphoric acid pretreatment does not affect the effectiveness of the pretreatment, and even Examples 2 to 4 show a promoting effect on the pretreatment effect, which is related to the decomposition of lignin in the pretreatment process assisted by the nucleophile.

[0045] In addition, the delignification rate of the pretreatment assisted by 2-naphthol, 3-hydroxy-2-naphthoic acid and 2-naphthol-7-sulfonic acid (Examples 2-4) was significantly higher than that of Comparative Example 1, indicating that these nucleophilic agents have great potential in promoting lignin decomposition in pretreatment. In addition, compared with 53.76% of glucan in the material of Comparative Example 1, the glucan content in the pretreated materials of Examples 1-4 was 51.19%, 49.88%, 51.55% and 52.86%, respectively, which may be related to the high content of ethanol extract when using nucleophilic additives to pretreat poplar wood with phosphoric acid, resulting in a decrease in the proportion of glucan.

[0046] The surface cellulose accessibility and hydrophobicity of the pretreated materials obtained in Examples 1 to 4 and Comparative Example 1 were tested respectively. The method for testing cellulose accessibility is as follows: the lignocellulosic material is exposed to direct red dye at 50°C and 150rpm for 24 hours, the substrate concentration is 1% (w / v), UV-vis is used to measure the absorbance of the supernatant after centrifugation in the sample and reference solution at 498nm, and a fitted Langmuir absorbance isotherm is established based on the corresponding adsorbed dye to evaluate the maximum adsorption amount of the dye as the substrate cellulose accessibility.

[0047] In addition, the method for determining the hydrophobicity of the material surface is to mix 2-10 g / L of the pretreated material and 40 mg / L of rose bengal in a 50 mM citric acid buffer with a pH of 4.8, and culture at 50°C and 150 rpm for 2 hours. Rose bengal is distributed in the liquid phase and on the surface of lignin and is separated by centrifugation. The content of free dye in the suspension is measured by an ultraviolet spectrophotometer at 543 nm to determine its absorbance value. The dye adsorbed on the lignin surface is calculated by the difference between the initial dye content and the free dye content. Partition quotient (PQ) = rose bengal content adsorbed on the material surface / rose bengal content dispersed in the culture medium. Plot PQ against lignin content. The slope of the straight line is considered to be the amount of lignin surface hydrophobicity (L / g). The results of cellulose accessibility and surface hydrophobicity of pretreated materials are shown in Table 3.

[0048] Table 3 HPLC quantitative analysis of monosaccharides and common monosaccharide degradation products in pretreatment solution

[0049] Material Type Cellulose accessibility (mg / g) Hydrophobicity (L / g) Example 1 201.01 0.12 Example 2 236.66 0.10 Example 3 296.12 0.09 Example 4 331.73 0.04 Comparative Example 1 237.07 0.12

[0050] As shown in Table 3, the cellulose accessibility of the pretreated materials in Example 3 and Example 4 was increased to 296.12 mg / g and 331.73 mg / g, which was significantly higher than that in Comparative Example 1.

[0051] Figure 1 In the figure, (a) is a scanning electron microscope image of the pretreated material of comparative example 1, (b) is a scanning electron microscope image of the pretreated material of example 1, (c) is a scanning electron microscope image of the pretreated material of example 2, (d) is a scanning electron microscope image of the pretreated material of example 3, and (e) is a scanning electron microscope image of the pretreated material of example 4. Figure 1 It can be seen that the pretreated materials of Examples 3 and 4 have a rougher surface than that of Comparative Example 1, which results in a higher enzyme digestibility.

[0052] In addition, compared with the hydrophobicity of 0.12 L / g in Comparative Example 1, the hydrophobicity of Examples 2 to 4 was reduced to 0.10 L / g, 0.09 L / g and 0.04 L / g. Since hydrophobic interaction is one of the most important reasons for the nonspecific adsorption of cellulase and lignin on the surface of the material, the lower surface hydrophobicity of the material assisted by the nucleophilic agent may also be related to the better substrate digestibility. In addition, the lower hydrophobicity of Examples 2 to 4 may be related to their higher delignification rate.

[0053] Analysis Example 2: Enzymatic hydrolysis performance of phosphoric acid pretreated materials with nucleophile addition

[0054] The pretreated materials obtained in Examples 1 to 4 and Comparative Example 1 were respectively hydrolyzed with 20 FPIU / g of cellulase (filter paper enzyme activity: 200 FPIU / g). The enzymatic hydrolysis conditions were 50 mL system, pH 4.8, 50 mM sodium citrate buffer, and the reaction was carried out on a shaker at 50 ° C and 150 rpm for 72 h. The enzymatic hydrolysis samples were extracted at different time points (0, 3, 6, 12, 24, 48 and 72 h) and analyzed by high performance liquid chromatography to determine the amount of glucose produced during the enzymatic hydrolysis process and calculate the enzymatic hydrolysis yield. The enzymatic hydrolysis yield was compared and analyzed. The results are as follows: Figure 2 shown.

[0055] The experimental results show that the enzymatic hydrolysis yield of the pretreated material of Comparative Example 1 is 66.15%, the enzymatic hydrolysis yields of Examples 1 to 3 are 71.41%, 84.23% and 95.83%, and the saccharification rate of Example 4 is even as high as 100%. The increase in the glucose yield of the pretreated material with the addition of nucleophilic agents, especially the glucose yield of Example 4 is increased to 100%, indicating that the nucleophilic additive is crucial to improving the enzymatic hydrolysis yield of poplar wood by phosphoric acid pretreatment, because it can improve the removal rate of lignin in the pretreated material and the accessibility of cellulase.

[0056] Analysis Example 3: Effect of Nucleophile Addition on Surface Crystal Structure and Element Distribution of Phosphoric Acid Pretreated Materials

[0057] The surface crystallinity and element distribution of the pretreated materials obtained in Examples 1 to 4 and Comparative Example 1 were analyzed respectively. First, the crystal structure of the materials was analyzed by X-ray diffraction (XRD) using an Ultima IV instrument, and the results are shown in Figure 3 In addition, for the cellulose crystallinity of different materials, the present invention analyzes the crystallinity (CrI-II) of cellulose II in the materials of Examples 1 to 4 and Comparative Example 1, and the analysis method is: detect and screen the materials below 200 mesh, and set the scattering angle (2θ) to scan at a scanning speed of 10° / min from 5° to 50°. The calculation formula of CrI-II is as follows:

[0058]

[0059] Where:

[0060] CrI represents the crystallinity index of cellulose II;

[0061] I total It stands for total intensity and refers to the sum of the intensities of all diffraction peaks within a specific angle range in X-ray diffraction (XRD) analysis.

[0062] I am It represents the amorphous intensity, that is, the diffraction peak intensity of the amorphous part in the XRD spectrum.

[0063] The results are shown in Table 4.

[0064] Among them, for the cellulose II in the material, I total is the maximum diffraction intensity of the crystal region at about 21.7°, I am is the minimum intensity of the peak in the amorphous region at about 16.0°.

[0065] Table 4 Crystallinity of cellulose II zone of pretreated materials

[0066] Material Type Crystallinity of cellulose II Example 1 16.68 Example 2 18.71 Example 3 32.59 Example 4 24.01 Comparative Example 1 12.09

[0067] like Figure 3 As shown, the addition of nucleophilic agents in phosphoric acid pretreatment did not change the characteristic diffraction peaks of cellulose in the pretreated poplar wood material, indicating that their crystalline structures remained unchanged. In addition, since different crystalline isomers of cellulose have different reaction probabilities during the saccharification process of cellulase hydrolysis, the reaction probability of cellulose II in the hydrolysis conversion is much higher than that of cellulose I. Table 4 shows the crystallinity of cellulose II in the XRD analysis of the pretreated materials obtained in Examples 1 to 4 and Comparative Example 1. The results of Table 4 show that the CrI-II of Examples 1 to 4 increased from 12.09 (Comparative Example 1) to 16.68, 18.71, 32.59 and 24.01. All nucleophilic additives in phosphoric acid pretreatment increased the CrI-II of the phosphoric acid pretreated material, and CrI-II is proportional to the saccharification efficiency of the treated material. Therefore, the results of CrI-II support the improvement of the enzymatic hydrolysis yield of the phosphoric acid pretreated material by nucleophilic additives. This may be because the addition of the nucleophilic agent expands the proportion of the active reaction area of ​​cellulose, so the enzymatic hydrolysis yields of Examples 1 to 4, especially the yields of Examples 3 and 4, are greatly improved.

[0068] In addition, the CrI-II of Example 4 (24.01) is relatively lower than that of Example 3 (32.59), while its enzymatic hydrolysis glucose yield (100.00%) is higher than that of Example 3 (95.83%). This may be because compared with Example 3 (29.35%, 296.12 mg / g, 0.09 L / g), Example 4 has a higher delignification rate (31.35%), cellulose accessibility (331.73 mg / g) and lower hydrophobicity (0.04 L / g). These other physicochemical properties may be more helpful to improve its enzymatic hydrolysis yield.

[0069] In addition, XPS analysis of the phosphoric acid pretreated material with nucleophile addition was performed using a monochromatic Al-Ka radiation source, with a hybrid trough lens configuration covering an area of ​​approximately 300 mm × 700 mm. The residual lignin content was quantified by analyzing the aliphatic carbon area on the surface of the material, and the degree of lignin surface coverage was inferred from the oxygen-carbon ratio (O / C). The results are shown in Figure 4As shown. Because the decrease in CC / CH peaks may indicate that the surface lignin of the material is removed, the CC / CH ratios of Examples 1 to 3 are reduced from 36.04% of Comparative Example 1 to 34.45%, 30.56% and 35.84%, respectively, which indicates that the surface lignin content of Examples 1 to 3 is less than that of Comparative Example 1, and therefore the enzymatic digestibility of Examples 1 to 3 is higher than that of Comparative Example 1 (71.41%, 84.23% and 95.83%, respectively, while Comparative Example 1 is 66.15%). However, Example 4 has the highest enzymatic hydrolysis yield (100%), but its CC / CH ratio (42.91%) is higher than the CC / CH ratios of all other Examples and Comparative Examples (30.56-36.04%), which may mean that the decomposed lignin attached to the surface of Example 4 may have promoted its enzymatic hydrolysis, thereby further improving rather than reducing the enzymatic digestibility of the material.

[0070] In summary, the present invention provides a biomass pretreatment method, which directly adds nucleophilic reagents during acid pretreatment, thereby improving the saccharification efficiency of acid-pretreated biomass raw materials, overcoming the defect of limited saccharification efficiency of pretreated biomass cellulose in existing acid pretreatment technologies, and at the same time improving the characteristics of the pretreated substrate, increasing the accessibility of cellulose, and improving the surface structure of the pretreated material, providing better conditions for further utilization of biomass.

Claims

1. A biomass pretreatment method, characterized in that: The following steps are involved: S1, immersing the crushed poplar wood in an acid solution at a solid-liquid ratio of 1:7 (w / v), and adding a nucleophilic reagent to the solution to react at 180°C; S2, after the reaction is completed, the reaction system in step S1 is cooled to room temperature, and solid-liquid separation is performed to obtain a pretreated solid; S3, rinsing the pretreated solid obtained in step S2, washing the substrate with distilled water until the pH value is close to neutral, and performing the rinsing process three times to obtain an acid-nucleophile pretreated material.

2. The biomass pretreatment method according to claim 1, characterized in that: The acid is phosphoric acid.

3. The biomass pretreatment method according to claim 2, characterized in that: The concentration of phosphoric acid was 1.5% (v / v).

4. The biomass pretreatment method according to claim 1, characterized in that: The nucleophilic agent is ascorbic acid, 2-naphthol, 3-hydroxy-2-naphthoic acid or 2-naphthol-7-sulfonic acid.

5. The biomass pretreatment method according to claim 4, characterized in that: The amount of the nucleophile added was 4% (w / w).

6. The biomass pretreatment method according to claim 1, characterized in that: The reaction time is 60 minutes.